Michael Field, Pre-Raphaelite: One Play and Two Fair Beginnings - Ana Parejo Vadillo (19, 2023)
This article examines the development of Pre-Raphaelitism into decadence by focusing on Michael Field, whose verse play Fair Rosamund was published twice, first in 1884 (by George Bell and Sons) and later in 1897 by the Vale Press of Charles Ricketts. The article focuses on the legend of the ‘Fair Rosamund’ and how it was treated by Pre-Raphaelite poets and painters, both male and female. Positioning the Michael Field poets as Pre-Raphaelites, the article looks at how this poetic drama articulated a different decadent beginning, one inspired by and in communion with painting.